SITUAÇÃO EPIDEMIOLÓGICA DA SÍFILIS CONGÊNITA EM SÃO LUÍS-MA NO SÉCULO XXI. - BARRETO, Ingrid Cabral (2019)
Syphilis is a chronic infectious disease that affects practically all organs and systems, and despite its effective and low cost treatment, it has remained a public health problem until the present day. The transmission of this disease occurs sexually and vertically, through the mother's placenta to the fetus. Due to the significant frequency of gestational and congenital syphilis in Brazil, the Northeast region and Maranhão, taking into account the complications caused by this disease in pregnant women and newborns, this study aims to evaluate the situation of congenital syphilis and determine the epidemiological profile of infection caused by Treponema pallidum in puerperal women and newborns. This is a cross-sectional, documentary and descriptive study, carried out in 3 Maternities of the city of São Luís. We used as source of data records of puerperal and newborn medical records from January 2015 to December 2018. Including 429 cases of gestational and congenital syphilis, 51.98% of the 25-year-old median puerperal women, 86.24% declared brown, with incomplete high school (26.34%). Most (81.38%) pregnant women had prenatal care, with inadequate treatment (58.51%). The profile of newborns with syphilis was 51% female, 89.23% declared by their parent as brown, 81.86% with nontreponemal reagent test. Regarding the clinical signs variable, 91.69% of the newborns were asymptomatic. As for gestational outcome 90.91% were alive. This research shows that syphilis in pregnancy is still a factor present and associated with vertical transmission. We highlight the importance of deepening comparative studies to better evaluate this important component of perinatal morbidity and mortality in the country scenario and in the state of Maranhão.